The Concept of The State in Islam: A Study of Maudhu'i's Interpretation - Sabrina Farah Fuadia; Raudotul Aini; Raka Meirwanto Soba; Asep Abdul Muhyi (Bulletin of Islamic Research, 2024)
This research aims to find out the concept of the state is in the Islamic world, more precisely using analysis of the Maudhu'i interpretation method. The method used in this research is a descriptive-analysis technique with more emphasis on the interpretation of verses related to the theme of the country. Islam began to recognize the existence of the concept of state as a political phenomenon that emerged after the collapse of the Ottoman Caliphate in 1924. If the word state institution is searched for in the Koran, it will never appear, but there is the word state which corresponds to this term, such as the word balad, qoryah, baldah, and others. These state concepts can be found in QS. Ibrahim verse 35, QS. Yaasin verse 13, and QS. Saba verse 15. The results of this research found that there was a correlation between these verses of the Koran and the importance of an institution in a country.